Elevated translocator protein in skull bone marrow is linked to human chronic pain - Mehrbod Mohammadian; Nikos Efthimiou; Katherin Gabriel; Ludovica Brusaferri; Joya Cooper-Hohn; Minhae Kim; Jennifer P. Murphy; Zeynab Alshelh; Grace Grmek; Jack H. Schnieders; Courtney A. Chane; Thomas G. Carmichael; et al. (Science Translational Medicine, 2026)
The skull bone marrow (SBM) is emerging as a critical hub for neuroimmune signaling, yet its role in chronic pain is unknown. Using integrated positron emission tomography/magnetic resonance imaging, here, we show that the levels of 18-kilodalton translocator protein (TSPO), a putative marker of immune cell density, are elevated in the SBM of individuals with chronic pain [ n = 125; chronic low back pain (cLBP), n = 88; knee osteoarthritis (KOA), n = 37] compared with healthy controls ( n = 22). These elevations were widespread, generally more pronounced for KOA than cLBP, associated with pain and pain-comorbid symptoms in partially segregated spatial patterns, and supported by preliminary immunohistochemical evidence in human SBM samples from a donor with a history of chronic pain (compared with a healthy donor). Because TSPO is highly expressed in myeloid cells, these results link SBM immune dysregulation with chronic pain and its associated psychological and functional impairments. These findings provide a strong rationale for investigating this previously overlooked structure, which remains largely underexplored in the context of pain.